2002
DOI: 10.1590/s0100-879x2002000400012
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxic median raphe lesions aggravate working memory storage performance deficits caused by scopolamine infusion into the dentate gyrus of the hippocampus in the inhibitory avoidance task in rats

Abstract: The interactions between the median raphe nucleus (MRN) serotonergic system and the septohippocampal muscarinic cholinergic system in the modulation of immediate working memory storage performance were investigated. Rats with sham or ibotenic acid lesions of the MRN were bilaterally implanted with cannulae in the dentate gyrus of the hippocampus and tested in a light/dark step-through inhibitory avoidance task in which response latency to enter the dark compartment immediately after the shock served as a measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Much research has focused on determining the behavioral contributions that the dentate gyrus makes to learning and memory. Numerous studies have shown that the DG is critical for spatial reference memory (Barbosa, Pontes, Ribeiro, Ribeiro, and Silva, 2012; Beselia, Maglakelidze, Chkhikvishvili, Burjanadze, and Dashniani, 2010; Gilbert, Kesner, and Lee, 2001; Hernandez-Rabaza, Hontecillas-Prieto, Velazquez-Sanchez, Ferragud, Perez-Villaba, Arcusa, Barcia, Trejo, and Canales, 2008; Hunsaker, Mooy, Swift, and Kesner, 2007; Jeltsch, Bertrand, Lazarus, and Cassel, 2001; Lee, Hunsaker, and Kesner, 2005a; Xavier, Oliveira-Filho, and Santos, 1999) and spatial working memory (Babar, Melik, and Ozgunen, 2002; Babar, Melik, Ozgunen, and Polat, 2002; Costa, Bueno, and Xavier, 2005; Hernandez-Rabaza, Barcia, Llorens-Martin, Trejo, and Canales, 2007; Jeltsch et al, 2001; Niewoehner, Single, Hvalby, Jensen, Meyer zum Alten Borgloh, Seeburg, Rawlins, Sprengel, and Bannerman, 2007; Xavier et al, 1999). In addition, the DG is involved in contextual learning and memory; manipulations that impair DG function lead to deficits in contextual memory and context discrimination (Daumas, Ceccom, Halley, Frances, and Lassalle, 2009; Hernandez-Rabaza et al, 2008; Lee and Kesner, 2004; McHugh, Jones, Quinn, Balthasar, Coppari, Elmquist, Lowell, Fanselow, Wilson, and Tonegawa, 2007).…”
Section: 0 Contribution Of the Hippocampus To Cognitive Processesmentioning
confidence: 99%
“…Much research has focused on determining the behavioral contributions that the dentate gyrus makes to learning and memory. Numerous studies have shown that the DG is critical for spatial reference memory (Barbosa, Pontes, Ribeiro, Ribeiro, and Silva, 2012; Beselia, Maglakelidze, Chkhikvishvili, Burjanadze, and Dashniani, 2010; Gilbert, Kesner, and Lee, 2001; Hernandez-Rabaza, Hontecillas-Prieto, Velazquez-Sanchez, Ferragud, Perez-Villaba, Arcusa, Barcia, Trejo, and Canales, 2008; Hunsaker, Mooy, Swift, and Kesner, 2007; Jeltsch, Bertrand, Lazarus, and Cassel, 2001; Lee, Hunsaker, and Kesner, 2005a; Xavier, Oliveira-Filho, and Santos, 1999) and spatial working memory (Babar, Melik, and Ozgunen, 2002; Babar, Melik, Ozgunen, and Polat, 2002; Costa, Bueno, and Xavier, 2005; Hernandez-Rabaza, Barcia, Llorens-Martin, Trejo, and Canales, 2007; Jeltsch et al, 2001; Niewoehner, Single, Hvalby, Jensen, Meyer zum Alten Borgloh, Seeburg, Rawlins, Sprengel, and Bannerman, 2007; Xavier et al, 1999). In addition, the DG is involved in contextual learning and memory; manipulations that impair DG function lead to deficits in contextual memory and context discrimination (Daumas, Ceccom, Halley, Frances, and Lassalle, 2009; Hernandez-Rabaza et al, 2008; Lee and Kesner, 2004; McHugh, Jones, Quinn, Balthasar, Coppari, Elmquist, Lowell, Fanselow, Wilson, and Tonegawa, 2007).…”
Section: 0 Contribution Of the Hippocampus To Cognitive Processesmentioning
confidence: 99%
“…DRN contains the greatest density of serotonergic neurons, with around 11500 in the rat, and MRN follows it with approximately 1100 [1]. A large body of evidence supports the role of the DRN and MRN in an extensive array of important functions, including stress response [2][3][4][5], pain control [6][7][8][9], reproductive functions and behaviour [10], food intake and obesity [11,12], aggressiveness [13,14], social interaction [15], motivation and reward [16,17], fear [18,19], learning and memory [20][21][22][23], motor activity [12], and the sleep-wake cycle physiology [24][25][26]. Additionally, the raphe nuclei play an important role in the physiopathology of several diseases, including major depression [27][28][29], anxiety, panic, obsessive compulsive disorder, eating disorders, phobias, drug addiction, and post-traumatic stress [30].…”
Section: Introductionmentioning
confidence: 99%